Bacteria growth monitoring system using ultrasonic sensors - H. N. A., Salwa; Sundaraj, Kenneth, Prof. Dr.; Azian Azamimi, Abdullah; Mohammed Zulkali, Mohammed Daud, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.